2022
DOI: 10.3390/cancers14215333
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Oncoproteins Confer Sensitivity to Cisplatin by Interfering with Epidermal Growth Factor Receptor Nuclear Trafficking Related to More Favorable Clinical Survival Outcomes in Non-Small Cell Lung Cancer

Abstract: High-risk human papillomavirus (HPV) infections and epidermal growth factor receptor (EGFR) expression have been reported to be associated with more favorable survival outcomes in lung adenocarcinoma patients. In this study, we utilized transfected HPV 16E5/16E6/16E7 H292 cells to investigate the mechanism of HPV oncoproteins interfering with EGFR nuclear trafficking related to a better response to cisplatin. Furthermore, we correlated HPV 16E6/18E6 expression and differentially localized EGFR expression with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…According to their results, HPV16E6/18E6 and EGFR expression in NSCLC correlates with a greater survival rate in older lung adenocarcinoma patients without brain metastasis, with a smoking history, and with wild-type EGFR status. Additionally, this group of patients demonstrated an increased sensitivity to cisplatin-based chemotherapy due to the action of HPV16E5/16E6/16E7 oncoproteins on EGFR nuclear trafficking [57]. Other data available in the literature further support these observations, showing better prognosis, higher survival rates [58], and longer metastatic-free survival [26] in HPV18-and 19-positive NSCLCs compared to negative forms.…”
Section: Prognostic Aspects Of Hpv Infection In Nsclcsupporting
confidence: 66%
See 3 more Smart Citations
“…According to their results, HPV16E6/18E6 and EGFR expression in NSCLC correlates with a greater survival rate in older lung adenocarcinoma patients without brain metastasis, with a smoking history, and with wild-type EGFR status. Additionally, this group of patients demonstrated an increased sensitivity to cisplatin-based chemotherapy due to the action of HPV16E5/16E6/16E7 oncoproteins on EGFR nuclear trafficking [57]. Other data available in the literature further support these observations, showing better prognosis, higher survival rates [58], and longer metastatic-free survival [26] in HPV18-and 19-positive NSCLCs compared to negative forms.…”
Section: Prognostic Aspects Of Hpv Infection In Nsclcsupporting
confidence: 66%
“…The underlying reasons behind the favorable prognosis associated with HPV infection in NSCLC remain unknown. A possible explanation could be derived from a recent study (October 2022), where Wang et al [57] showed how HPV immortalizes cancer cells not only by inhibiting tumor suppressors (Rb and p53) but also by activating the EGFR pathway. According to their results, HPV16E6/18E6 and EGFR expression in NSCLC correlates with a greater survival rate in older lung adenocarcinoma patients without brain metastasis, with a smoking history, and with wild-type EGFR status.…”
Section: Prognostic Aspects Of Hpv Infection In Nsclcmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection of HPV DNA has been repeatedly reported in lung tumors worldwide [ 33 , 34 , 35 , 36 ], and while the association between infection and tumor progression is unclear, a recent study developed by Wang and collaborators investigated the possible interference of oncoproteins E5, E6, and E7 of HPV-16 transfected in H292 cells in the expression of the nuclear epidermal growth factor receptor (EGFR), where higher levels of EGFR were associated with greater sensitivity to cisplatin, a chemotherapeutic widely used to treat cancers [ 37 ].…”
Section: Cancers Related To Hpv Infection and Classic Treatment Strat...mentioning
confidence: 99%